NANOSTRUCTURES MANAGEMENT TECHNOLOGY TO REDUCE THE FIRE RISK IN THE OIL AND GAS INDUSTRY: PERFORMANCE, FEATURES AND IMPLEMENTATION - Ivanov, Aleksey V.; Dali, Farid A.; Ivakhnyuk, Grigoriy K.; Skripnick, Igor L.; Simonova, Marina A. (Journal of Applied Engineering Science, 2021)
Oil and gas enterprises are characterized by an increased fire risk. There is high probability of occurrence and spread of large fires when oil production and processing, transportation and storage of oil products occurs. There is high probability of large fires during the oil production, oil processing and during the transportation and storage of petroleum products. New materials created using nanotechnology principles are needed to improve the efficiency of fire prevention and extinguishing systems. The technology for controlling the properties and performance characteristics of nanofluids based on liquid hydrocarbons and water is based on the methods of functionalization and interaction of clusters of the base liquid and multilayer carbon nanotubes, methods for stabilizing nanofluids, for changing the thermophysical, rheological and electrostatic properties of substances and materials on their basis. The proposed technology makes it possible to create nanomaterials based on various scenarios for the development of emergency situations and to apply them to reduce fire risk at oil and gas facilities.